EKSPERIMENTASI PENDEKATAN CTL BERBANTUAN MEDIA IJS DALAM MENGOPTIMALKAN KECERDASAN LINGUISTIK SISWA SEKOLAH DASAR - Wiranti, Dwiana Asih; Sarie, Fitria Novita (Universitas Muria Kudus, 2019)
An experimental research has been successfully carried out in grade I at SD AL-Islam Pengkol and SDN 1 Pengkol Jepara. The implementation of CTL approach by IJS (Innovative Javanese Song) media is used to optimize linguistic abilities and learning outcomes in science learning. This research applies an experimental method to the type of non-equivalent control group design. The results showed a percentage of linguistic ability scores seen from the development of CTL learning by IJS media. Student learning outcomes have also increased. Cognitive test results show an average classical completeness of 90-95%. The gain score test results are 0.75 with a high category. The t-test results showed that the t-test was 8.619, greater than the t-table, 2.021. Affective learning outcomes show an average classical completeness of 80-82%. Psychomotor learning outcomes show an average classical completeness of 82%. It can be concluded that there are significant differences in linguistic abilities and learning outcomes in science learning with the CTL approach using IJS media. Therefore the teacher can develop this media on learning other material